Effect of a thermal care bundle on the prevention, detection and treatment of perioperative inadvertent hypothermia. Issue 5 (1st February 2018) - Duff, Jed; Walker, Kim; Edward, Karen‐Leigh; Ralph, Nicholas; Giandinoto, Jo‐Ann; Alexander, Kimberley; Gow, Jeff; Stephenson, John
Abstract : Aims and objectives: To improve the prevention, detection and treatment of perioperative inadvertent hypothermia in adult surgical patients by implementing a Thermal Care Bundle. Background: Keeping patients normothermic perioperatively prevents adverse surgical outcomes. Hypothermia leads to serious complications including increased risk of surgical bleeding, surgical site infections and morbid cardiac events. The Thermal Care Bundle consists of three elements: (i) assess risk; (ii) record temperature; and (iii) actively warm. Design: A pre‐ and postimplementation study was conducted to determine the impact of the Thermal Care Bundle on the prevention, detection and treatment of perioperative inadvertent hypothermia. Methods: The Thermal Care Bundle was implemented using an adapted version of the Institute of Healthcare Improvement's Breakthrough Series Collaborative Model. Data were collected from auditing medical records. Results: Data from 729 patients (pre‐implementation: n  = 351; postimplementation: n  = 378) at four sites were collected between December 2014–January 2016. Improvements were recorded in the percentage of patients with a risk assessment; at least one documented temperature recording per perioperative stage; and appropriate active warming. Despite this, the overall incidence of perioperative inadvertent hypothermia increased postimplementation. Conclusion: The Thermal Care Bundle facilitated improved management of perioperative inadvertent hypothermia through increased risk assessment, temperature recording and active warming but did not impact on perioperative inadvertent hypothermia incidence. Increased temperature recording may have more accurately revealed the true extent of perioperative inadvertent hypothermia in this population. Relevance to clinical practice: This study showed that a collaborative, context specific implementation method, such as the IHI Breakthrough Series Model, is effective at improving practices, which can improve thermal care.